Disparities in heart failure between White, Black, and Hispanic young adults: insights from the National Health and Nutrition Examination Survey - Khawaja M. Talha; Talal Almas; Abdul Mannan Khan Minhas; Husam Salah; Adeena Jamil; Heather M. Johnson; Vardhmaan Jain; Steve Antoine; Sadiya S. Khan; Muhammad Shahzeb Khan (Therapeutic Advances in Cardiovascular Disease, 2024)
Background: The prevalence of heart failure (HF) is increasing among young adults in the United States with pervasive racial and ethnic differences in this population. Objective: To evaluate contemporary associations between race and ethnicity, clinical comorbidities, and outcomes among young to middle-aged adults with HF. Methods: A retrospective analysis was performed using the National Health and Nutrition Examination Survey. All participants with a self-report of HF aged 20–64 years from 2005 to 2018 were included and stratified by race and ethnicity [non-Hispanic (NH) Whites, NH Blacks, and Hispanics]. Data on baseline characteristics including age, sex, marital status, citizenship, education level, body mass index, insurance, waist circumference, cigarette smoking, marijuana use, and relevant clinical comorbidities were included. Weighted logistic regression was performed to estimate adjusted odds ratios (aOR) to determine the association of race and ethnicity with HF. Cox proportional-hazards models were used to assess the association of race and ethnicity with all-cause and cardiac mortality. Results: A total of 1,940,447 young to middle-aged adults had self-reported HF between 2005 and 2018, of whom 61% were NH White, 40% were NH Black, and 22% were Hispanic. When compared with NH White adults, NH Black adults had higher odds of HF adjusted for age, sex, insurance status, marital status, education level, citizenship status, and clinical comorbidities (adjusted aOR 2.63, 95% CI: 1.71–4.05, p  < 0.001). There was no significant difference in the odds of HF between Hispanic and NH White adults (aOR 1.18, 95% CI: 0.64–2.18, p  = 0.585). NH Black adults had higher mean systolic and diastolic blood pressure, and a comparable or lower burden of cardiovascular and non-cardiovascular clinical comorbidities compared with NH White and Hispanic adults. No statistical significance was noted by race and ethnicity for all-cause and cardiac mortality during a follow-up of 5 years. Conclusion: NH Black young to middle-aged adults were more likely to have HF which may be related to higher blood pressure given the largely similar burden of clinically relevant comorbidities compared with other racial and ethnic groups.